Dip Quick Staining Modified for Morphological Evaluation to Equine Spermatozoa - Segabinazzi, Lorenzo Garrido [UNESP]; Mercês Chaves, Luis Fernando [UNESP]; Araujo, Endrigo Adonis [UNESP]; Nunes de Oliveira, Sidnei [UNESP]; Pena de Andrade Junior, Luiz Roberto [UNESP]; Cardoso Okada, Carolina Tieme [UNESP]; de Paula Andrade, Veridiana [UNESP]; de Paula Freitas Dell'Aqua, Camila [UNESP]; Papa, Frederico Ozanam [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2017)
Morphological analysis of the sperm cells were accomplished from 19 stallions comparing six different techniques (DIC, Karras, Eosin-Nigrosin, Dip Quick 5′, Dip Quick modified, Dip Quick) in order to verify the possibility of using a modification of Dip Quick stain technique to evaluate the morphology of equine semen. Data of sperm morphology were evaluated using Kolmogorov-Smirnov (KS) normality test. Parametric continuous data were compared for ANOVA followed by the Tukey test and non-parametric dates, for Kruskal-Wallis test followed by the Dunns test. Significant differences were considered when P < .05. Pearson product-correlation procedure was used to test the correlation between technics. High correlation were considered when r ≥ 0.7, moderate correlation when r ≥ 0.5 but r < 0.7 and poor correlation when r < 0.5. The proposed technique did not show difference (P >.05) from other techniques to morphological assessment. However, the usual Dip quick technique showed to be less efficient (P <.05) to evaluated the sperm morphology defects, especially for the display of abnormal heads, distal and proximal droplets. A High correlation was observed among techniques in the evaluation of total number of defects, but when specific sperm defects of each segment were measured the Dip Quick modified showed a high correlation compared with the usual technics, different results from the Dip Quick technic that showed a moderate correlation on the evaluation of distal and proximal droplets and poor correlation on abnormal heads evaluation. We can conclude that the modification of the Dip Quip technique improved the quality of smear for the evaluation of equine sperm morphology.
Keywords: Dip Quick stain; Equine spermatozoa; Morphology; Semen; Stallion